2010
DOI: 10.1149/2.f03101if
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Corrosion of Metals

Abstract: Pitting corrosion of metals is one of the most important electrochemical corrosion phenomena. Corrosion of steel reinforcement in concrete is always in the news, and it starts off as pitting, caused by chloride ions-so it is feasible that pitting is the most costly form of corrosion. Such an assessment might not be the same in every decade, and it is hard to measure the cost of corrosion Synthetic Diamond: Emerging CVD Science and Technology Edited by K. E. Spear and J. P. Dismukes (1994) 688 pages. ISBN 978… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…This basic idea has proven extremely powerful in helping to understand many of the characteristics of pitting corrosion 2 . Building on Galvele's early model, it has been shown 3,4 that metastable pits in 304 stainless steel propagate such that i.x increases with time, and that once this exceeds ~3 mA cm -1 then they are able to survive the complete loss of their porous cover and can be considered stable.…”
Section: Introductionmentioning
confidence: 99%
“…This basic idea has proven extremely powerful in helping to understand many of the characteristics of pitting corrosion 2 . Building on Galvele's early model, it has been shown 3,4 that metastable pits in 304 stainless steel propagate such that i.x increases with time, and that once this exceeds ~3 mA cm -1 then they are able to survive the complete loss of their porous cover and can be considered stable.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies of pitting corrosion in NaCl solutions, E b has been found to exhibit a negative logarithmic dependence on the chloride concentration, with the proportionality constant generally being in the range 60–90 mV . In the case of 304 stainless steel, for example, the proportionality constant is 88 mV .…”
Section: Discussionmentioning
confidence: 98%
“…The two corrosion phenomena, pitting corrosion and the galvanic corrosion, can be correlated in consideration of the pit development stages [35,36]. The pitting corrosion is initiated by the breakdown of the passive film.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this paper, the pitting corrosion resistance of the DSS2507 alloy was assessed based on the E pit level, and that was determined as the potential point at which the stable pit was A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 16 initiated and began to grow. During the stable pit growth in Fe-based metals, the electrolyte inside the occluded pit becomes acidified because of the hydrolysis reaction [35,36]. Thus, inside the pit, the bare surface of the metal without the passive film is exposed to the acidified solution.…”
Section: Accepted Manuscriptmentioning
confidence: 99%